Phase angle is an indicator of GLIM-diagnosed malnutrition in patients undergoing major pancreatic and biliary surgery - Lijuan Wang; Pengxue Li; Yifu Hu; Bo Cheng; Lei Li; Lili Ding; Jinghai Song; Junmin Wei; Jingyong Xu (Journal of Pancreatology)
Objective:. The aim of this study is to elucidate the correlation between phase angle and malnutrition, and to determine the malnutrition cutoff points based on phase angle in patients undergoing major pancreatic and biliary surgery. Methods:. This is a cross-sectional study analyzing the prospective database of the Department of Hepatopancreatobiliary Surgery at Beijing Hospital, China, from December 2020 to September 2023. Basal data, diet surveys, anthropometry, and body composition were recorded. Phase angle was measured with the InBody 720. The Global Leadership Initiative on Malnutrition (GLIM) criteria were used to diagnose malnutrition. Subgroup analyses were conducted by stratifying age and pancreatic cancer. Results:. A total of 185 consecutive cases were included, with a mean age of 63.66 ± 11.96 years. 63.8% (118/185) of the participants were aged 60 years or older, and 43.8% (81/185) were diagnosed with pancreatic cancer. The prevalence of malnutrition was 62.2% among all subjects, 67.8% among the elderly, and 69.1% among pancreatic cancer patients. Phase angle was significantly lower in the malnourished group than in the normal group. Positive correlations were found between phase angle and body mass index (BMI), appendicular skeletal muscle mass index (ASMI), fat-free mass index (FFMI), fat-free mass, total energy intake, grip strength, calf circumference, 6-m timed walk speed, total protein, albumin, and prealbumin. Among all the subjects, participants with a lower phase angle were significantly more likely to suffer from malnutrition than their control group, with a 1.611 times higher risk (95% confidence interval [CI]: 1.013–2.562, P = .044). The cutoff points of the phase angle for determining malnutrition were 4.82 in men (sensitivity 0.744, specificity 0.571, area under the curve 0.667, 95% CI: 0.567–0.766, P = .003), and 4.54 in women (sensitivity 0.750, specificity 0.711, area under the curve 0.757, 95% CI: 0.644–0.869, P < .001). In the subgroup analyses of elderly and pancreatic cancer patients, we obtained consistent results with statistical significance and identified corresponding cutoff points. Conclusion:. The present study suggests that the phase angle could be a valid, useful, and simple indicator of malnutrition in patients undergoing major pancreatic and biliary surgery.